A selective carotid artery shunting for carotid endarterectomy: prospective MR DWI monitoring of embolization in a group of 754 patients - Orlický, Michal; Vachata, Petr; Bartoš, Robert; Waldauf, Petr; Sameš, Martin (Journal of neurological surgery. Part A, Central European neurosurgery, 2015)
BACKGROUND: Intraoperative use of the intraluminal shunt may reduce the risk of a stroke by reducing cerebral blood flow compromise, but it may also increase the risk of atherosclerotic arterial wall damage with subsequent stroke during carotid endarterectomy (CEA). There is still no evidence to support routine or selective shunting. MATERIAL AND METHODS: A total of 754 CEAs were performed in a prospective study from 2005 to 2011 at our department. All procedures were done under regional anesthesia with selective carotid artery shunting according to neurologic status after internal carotid artery clamping. Magnetic resonance (MR) evaluation of brain parenchyma using diffusion-weighed imaging (DWI) sequence was performed upon hospital admission and 24 hours after the surgical procedure. Acute new MR DWI lesions were evaluated according to the classification published by Szabo et al. A routine neurologic evaluation was recorded as well. RESULTS: The intraluminal shunt was used in 46 of 754 patients (6.1%). A new ischemic lesion was detected in 45 patients (6%). Most of these lesions were neurologically asymptomatic (80%). A new lesion on MR DWI in the subgroup of shunted patients was detected in 15 cases (32.6%) and in the subgroup of nonshunted patients in 30 cases (4.2%). Most of these lesions were due to embolization or hypoperfusion during shunt insertion. CONCLUSION: Use of the intraluminal shunt was the most important risk factor for the new MR DWI lesion in the entire group of CEAs. Results support the strategy of a selective use of intraluminal shunts.
Keywords: karotická endarterektomie; arteriae carotides; výsledek terapie; cévní mozková příhoda; difuzní magnetická rezonance; lidé; Stroke; Treatment Outcome; prognóza; Humans; Risk Factors; předoperační období; Carotid Arteries; Carotid Stenosis; stenóza arteria carotis; Diffusion Magnetic Resonance Imaging; Endarterectomy, Carotid; rizikové faktory; Prognosis; Preoperative Period